- #26

- 59

- 10

ok, I've thought about it about. The goal of this proof should be to show that ##y \in f(f^{-1}(E) \iff y \in E##

So to start with ##y \in f(f^{-1}(E)##. ##y = f(x)## for some ##x \in f^{-1}(E)##

Or maybe since it is surjective, it is best to start with ##y \in E## so that we can show that there's at least one x in ##f^{-1}(E)##, such that ##f(x) = y##.

So to start with ##y \in f(f^{-1}(E)##. ##y = f(x)## for some ##x \in f^{-1}(E)##

Or maybe since it is surjective, it is best to start with ##y \in E## so that we can show that there's at least one x in ##f^{-1}(E)##, such that ##f(x) = y##.

Last edited: